Perbandingan Teknik Budidaya Rumput Laut (Gracilaria verrucosa) dengan Metode Longline dan Broadcast di PT. Rejeki Bintang Samudra, Sidoarjo, Jawa Timur - Puteri, Ratih Rizqya; Pankito, Laurent Mercy; Mediana, Wahyu; Zahroh, Fika; Ramadhaniah, Ratih; Priyanto, Galih; Mukminin, Amirul (Universitas Batangahari Jambi, 2026)
Indonesia remains one of the world's largest seaweed exporters; however, the optimisation of added value through the downstreaming of Gracilaria verrucosa still faces challenges regarding cultivation efficiency. This research aims to analyse the comparative cultivation techniques of the broadcast and longline methods, as well as the potential of polyculture systems at PT Rejeki Bintang Samudra. The parameters tested included biomass, Specific Growth Rate (SGR), and harvest productivity.The results indicated that both methods delivered superior performance, with biomass reaching 9,550 grams and an SGR of 3.13% at DOC 50. Productivity analysis based on harvest yields showed significant fluctuations at each sampling point, with a total accumulated weight of 118,740 kg from a total of 150 sacks. The highest productivity was recorded at the 40th sampling at 810.62 kg/sack, whilst the average total productivity stood at 791.6 kg/sack. Although both methods demonstrated excellent results, the reliance on monoculture systems remains a constraint for scalability. Consequently, the integration of Gracilaria verrucosa into a polyculture system with milkfish is recommended as a strategy for an aquaculture transformation that is more adaptive, sustainable, and of higher economic value.